Analyzing the Community's Perspective on the Relationship Between Landscape Characteristics and the Importance of Toponym: a study case of Matsudo-shi, Chiba-ken, Japan. Issue 1 (May 2020) - Imara, I D; Furuya, K; Nurhayati,
Abstract: It is a common knowledge that every location on earth has its own names, called toponym. Essentially, the name functions as a place identity, distinguishing one place to another based on the community that lives in the area. From the perspective of the community in Japan, toponym is dynamic: it is a cultural heritage, but the name might change, become new, or disappear. This happened because local authorities assumed they own the toponym (there is no enforcement, and it is free to change or even to sale). There are 5 origin theories for toponym in Japan: terrain, Ainu language, disaster, traveller/direction, and others. Matsudo-shi is a city made from merging other small cities into one. In the case of the toponym of this city, there are 3 theory possibilities that emerged based on literatures. Even so, it is very difficult to determine which one is true, caused by the lack of records, other supporting literatures, and researcher's language ability. Furthermore, the landscape characteristics that reflected the origin of the name in the said area also need to be defined and analysed further. This research has the purpose to trace the information about the area toponym: the origin of the name, to analyse the community's perceptions and preferences, and to evaluate the landscape characteristics. It was conducted with three kinds of studies: literature study, field survey, and questionnaires. The result of this research is a general understanding towards toponym and the community perspective related to this in Japan. The conclusion for the result was the respondents seem to value characteristic of Matsudo-shi very much and thought that some enhancement based on the toponym history is recommended for the next town management planning.